Claude Jutra's Surfacing (1981) through visual spectacles: Framing female body, voyeurism and paranoia. (1st May 2020) - Ishaque, Nausheen; Riaz, Saba
This article examines Claude Jutra's 1981 film adaptation of Margaret Atwood's Surfacing in terms of its focus on female body, voyeurism and paranoia. The psychoanalytic perspective of the feminist film theory, with its emphasis on visual pleasure, narcissism, the male gaze, scopophilia, fetishization of the female, the oedipal nature of the narrative and female subjectivity, provides a pragmatic groundwork for the theoretical underpinning of this study. In the same way, the film apparatus, such as editing and camera work, provides a semiotic impetus to the spectator to identify with the perfect male, and not with the distorted female. With its focus on various scenes, generic codes and aspects of the film, the paper furthermore sees how Jutra's production validates the prejudices of the classical film narrative in the context of the female image, sexual difference, female desire and stereotyped female paranoia. Despite its narrative focus on the quest of a female protagonist, Jutra's film conforms to the traditional model of the classical cinema wherein the woman is no more than a signifier – an entity that signifies things in relation to men only.